二战前的新加坡女子华文教育之初探 = The preliminary study of pre war female Chinese education in Singapore - 王晓贤 Ong, Xiao Xian (2012)
殖民地时代的新加坡女子华文教育起步较晚。从19世纪至战前，其发展过程曲折。早期，女子华文教育受到中国女子教育改革的影响。后来，英国殖民政府插手管制华校，女子华文教育也遭受波及。克服困难后，女子华文教育渐渐发展起来，却因战争爆发而停滞。本文针对二战前的新加坡，研究了女子华文教育的发展的速度及情况。本文分为两大部分，首先论述了女子华文教育起步的相关背景，然后正式进入主题。本区华文教育受到中国新政鼓舞而迅速发展，正当华校蓬勃发展之际，女子华文教育却被大众忽略了。本文从学校所面对的外部及内部问题，分析了女子华教缓步发展的矛盾现象。女子教育工作者提升教育素质，互相合作，并且时常更改制度以配合本地华社，女子华文教育终于得到了新的发展。最后，第六章是结论。Female Chinese education in Singapore during colonial years started out fairly late. From the 19th century to World War II, its development was not smooth-sailing. In its early days, female Chinese education was in synchrony with China’s female education reforms. Then, the British government decided to interfere with the activities in Chinese schools including female Chinese schools. Faced with difficulties, our pioneers overcame them. However, it was the outbreak of war that led to the abrupt standstill of the prospering female Chinese education in Singapore. My project aims to discuss the development of female Chinese education in Singapore before World War II. There are two major parts to this thesis. I will provide the background knowledge on the beginning of female education in Singapore. After which, I will go into evaluating its development. China’s new political changes had brought about the rapid expansion of Chinese education, but the development of female education was still overlooked. I will address the external and internal factors pertaining to its slow growth. Our forefathers’ persistence and enthusiasm towards female education was most evident through the improvement of the standard of local female education. They collaborated with one another and modified the syllabus to suit the local Chinese. Finally, we saw a new direction in female Chinese education. Chapter Six gives a conclusion and a summary.